Los blogs y nuevos medios implementados en la rendición de cuentas de los asambleístas 2013-2015 - Luna Roldán, Silvana Ibeth (2015)
The term accountability and its connection to politics, is being used frequently nowadays, the term refers to the obligation that political actors, who are in power have to spread awareness about their activities. In addition, an analysis was performed, specifically on social and vertical accountability, as a result,it indicates that new communication tools improve participation, access to information about political actor’s activities and it promotes government transparency. Therefore, this research sought to make an analysis on the institutionalblogs as a communication tool, implemented in Ecuador’s National Assembly which represents the legislative branch, along with,an analysis on the new communication tools that are being used by the representatives, in order to establish, whether these tools function as mechanisms of accountability, and if thiscan improve participation. In addition, the methodology consisted in the perceptions of the representatives, obtained through a series of interviews with questions related to accountability, blogs and the new communication tools, that are being used…